Thermal control and generation of charge currents in coupled quantum dots. Issue 3 (9th December 2015) - Thierschmann, Holger; Arnold, Fabian; Mittermüller, Marcel; Maier, Luis; Heyn, Christian; Hansen, Wolfang; Buhmann, Hartmut; Molenkamp, Laurens W.
Abstract: This article reviews recent thermoelectric experiments on quantum dot (QD) systems. The experiments focus on two types of inter‐dot coupling: tunnel coupling and Coulomb coupling. Tunnel‐coupled QDs allow particles to be exchanged between the attached reservoirs via the QD system. Hence, an applied temperature bias results in a thermovoltage. When being investigated as a function of QD energies, this leads to the thermopower stability diagram. Here, largest thermovoltage is observed in the regions of the triple points. In a QD system which exhibits only capacitive inter‐dot coupling, electron transfer is suppressed. Such a device is studied in a three‐terminal geometry: while one QD connects to the heat reservoir, the other one can exchange electrons with two reservoirs at a lower temperature. When the symmetry of the tunneling coefficients in the cold system is broken, the device becomes an energy harvester: thermal energy is extracted from the heat reservoir and is converted into a directed charge current between the two cold reservoirs. This review illustrates the large potential of multi‐QD devices for thermoelectrics and thermal management at the nanometer‐scale. Abstract : In this article, the authors review the thermoelectric properties of a coupled quantum dot system which can be viewed as an artificial molecule. The first part presents the measurement of the thermopower generated by such a system located between a hot and a cold reservoir. In the second part it is discussed how coupled quantum dots can be used to extract energy from the hot reservoir and convert it into a directed current without particle exchange.